Oligomeric structure of proclavaminic acid amidino hydrolase: evolution of a hydrolytic enzyme in clavulanic acid biosynthesis. - Elkins, J; Clifton, I; Hernández, H; Doan, L; Robinson, C; Schofield, C; Hewitson, K (2002)
During biosynthesis of the clinically used beta-lactamase inhibitor clavulanic acid, one of the three steps catalysed by clavaminic acid synthase is separated from the other two by a step catalysed by proclavaminic acid amidino hydrolase (PAH), in which the guanidino group of an intermediate is hydrolysed to give proclavaminic acid and urea. PAH shows considerable sequence homology with the primary metabolic arginases, which hydrolyse arginine to ornithine and urea, but does not accept arginine as a substrate. Like other members of the bacterial sub-family of arginases, PAH is hexameric in solution and requires Mn2+ ions for activity. Other metal ions, including Co2+, can substitute for Mn2+. Two new substrates for PAH were identified, N-acetyl-(L)-arginine and (3R)-hydroxy-N-acetyl-(L)-arginine. Crystal structures of PAH from Streptomyces clavuligerus (at 1.75 A and 2.45 A resolution, where 1 A=0.1 nm) imply how it binds beta-lactams rather than the amino acid substrate of the arginases from which it evolved. The structures also suggest how PAH selects for a particular alcohol intermediate in the clavam biosynthesis pathway. As observed for the arginases, each PAH monomer consists of a core of beta-strands surrounded by alpha-helices, and its active site contains a di-Mn2+ centre with a bridging water molecule responsible for hydrolytic attack on to the guanidino group of the substrate. Comparison of structures obtained under different conditions reveals different conformations of a flexible loop, which must move to allow substrate binding.